Complete mitochondrial genome of the freshwater prawn Palaemon capensis (Crustacea: Palaemonidae) - Wood, LE; De Grave, S; van Heerden, CJ; Daniels, SR (Taylor and Francis Open, 2017)
The complete mitogenome of Palaemon capensis is presented here. The mitogenome is 15,925 bp in length and comprises 13 protein coding genes, 2 ribosomal subunit genes, 22 transfer RNAs, and a non-coding AT-rich region. The PCGs were used to perform a phylogenetic analysis together with other Caridea representatives with mitogenome data from GenBank, placing P. capensis sister to a clade comprising P. serenus, P. gravieri, and P. carinicauda in the family Palaemonidae.